PENGARUH PUPUK HAYATI CAIR TERHADAP PRODUKSI BUDIDAYA BAWANG MERAH DI KECAMATAN SEDAN - Nugroho, Fitra Margi; Khoyriyah, Nafiatul (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
The addition of biological fertilizers is expected to affect the growth and yield of shallot bulbs. In addition to having a positive impact on soil fertility, it also has an impact on efficiency if the microbial ecosystem has developed so that the use of external inputs such as chemical fertilizers can be suppressed. This study aims to describe the implementation of shallot cultivation in Sedan District and to determine the effect of using biological fertilizers in increasing shallot production. The research was carried out in the BPP Sedan experimental field from August 1 to October 9, 2022. Treatment consists of Non-Biological Fertilizer (NPH) and Treatment With Biological Fertilizer (DPH). Observations were carried out at the age of the plants 7 hst, 14 hst, 21 hst, 28 hst, 35 hst, and 42 hst. Plant performance includes leaf length, number of leaves and number of tillers. Yields were weighed at harvest at each point. The results showed that there were differences in the length of the leaves, the number of tillers and the weight of the shallot bulbs. The conclusion is the addition of biological fertilizers increases productivity significantly.